Production of pure oxygen from BSCF hollow fiber membranes using steam sweep - Leo, A.; Liu, Shaomin; da Costa, J. (Pergamon, 2011)
In this work, BSCF hollow fiber membranes made from a phase inversion/sintering technique produced high purity oxygen (>99.5%) at high flow rate of 9.52 ml min−1 cm−2 at 950 °C using a steam sweep gas. Long term exposure to steam sweep gas revealed loss of performance. For instance, oxygen flux remained stable up to 20 h, though undergoing a significant reduction afterwards. Similarly, the oxygen purity reduced after 40 h testing, though less significantly as oxygen fluxes. We found that steam leached the elements of BSCF, mainly forming an extra layer of insoluble carbonates of barium and strontium. This was attributed to the reaction of the perovskite with carboxylic acid ever present in steam. In addition, steam exposure at high temperature reduced the area of diffraction and crystallite sizes of the reflective planes of the BSCF membrane, thus indicating that the steam exposure deteriorated the crystal ordering. The membrane area exposed to steam become porous while covered with a porous layer of carbonates of barium and strontium, thus limiting the oxygen surface kinetics and explaining the oxygen flux reduction over time.